The Thoughts of Kiai Hasyim Asy’ari on the Concept of Women’s Education - Maulana, Dias; Nurwulan, Vita (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2025)
Education for women in Islam remains a relevant issue, especially considering ongoing discrimination and stereotyping in society. In this context, the thoughts of Kiai Hasyim Asy’ari regarding women’s education are essential to examine in order to understand his perspective on the equal right to education for both men and women. This study aims to analyze Kiai Hasyim’s concept of women’s education. Using qualitative methods with a literature review approach, the research collects and analyzes data from various sources regarding Kiai Hasyim’s thoughts. The findings indicate that Kiai Hasyim emphasizes the importance of education for women as a right equal to that of men and supports the implementation of inclusive education, where women play a role as educators and character developers in families and society. The contribution of this research is to highlight Kiai Hasyim’s thoughts that are relevant to current efforts to enhance women’s education in Indonesia.